Transformasi Digital dan Pertumbuhan E-Commerce: Dampak, Peluang, dan Tantangan di Era Modern - Edita Rachma Kamila; Anala Ilfi Xena Andini; Tutie Azzahra (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Digital transformation has brought changes in the business world, especially in the e-commerce sector which is experiencing rapid growth. The existence of e-commerce supports operational efficiency, accelerates transactions, and expands market access. By 2022, this sector will contribute 64.5% to Indonesia's total digital economy. However, digital transformation also poses challenges. This study aims to explore the impact, opportunities and challenges commonly faced by businesses in facing this modern era of digitalization. This research uses a qualitative approach, secondary data obtained from various sources such as scientific journals, industry reports, and publications and then analyzed inductively with content analysis techniques. The results show that digitalization provides great opportunities for businesses to reach a wider market, optimize operational efficiency, and increase customer engagement. However, there are also challenges such as data security issues, intensified competition, and the need for large technology investments. This research is expected to provide insights for businesses and relevant stakeholders in adopting the right strategies to maximize digital opportunities while overcoming various challenges.